1995
DOI: 10.1029/93jd03316
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric aerosol trace element chemistry at Mauna Loa Observatory: 1. 1979–1985

Abstract: Aerosol samples were collected at the Mauna Loa Observatory in Hawaii from February 1979 to May 1985. The samples were analyzed via instrumental neutron activation analysis (INAA) for up to 47 elements and via ion chromatography for sulfate. The data are dominated by crustal dust that arrives via long‐range transport from Asia each spring, thus creating a “dust season.” Of the 47 elements detected, 37 have a notably higher mass average during the dust season. The data record is explored using enrichment factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Apparently, dust from long-range transport and scavenging by precipitation caused large variations in Al concentration. Large temporal variability for mineral-derived elements was consistent with other observations in remote areas downwind and big desert countries, such as northeastern China , Hong Kong , and Hawaii (Zieman et al 1995). In an usual case observed by Kim and Park (2001), a sharp decrease in total PM concentration by one order of magnitude (from approx.…”
Section: Discussionsupporting
confidence: 74%
“…Apparently, dust from long-range transport and scavenging by precipitation caused large variations in Al concentration. Large temporal variability for mineral-derived elements was consistent with other observations in remote areas downwind and big desert countries, such as northeastern China , Hong Kong , and Hawaii (Zieman et al 1995). In an usual case observed by Kim and Park (2001), a sharp decrease in total PM concentration by one order of magnitude (from approx.…”
Section: Discussionsupporting
confidence: 74%
“…Weak dust layers occur in the FT over Japan during periods with no evident dust outbreaks or even in seasons other than spring (e.g., Iwasaka et al 1983). Asian dust events have been observed at FWS (Suzuki et al 2008(Suzuki et al , 2010, MLO (Bodhaine 1995;Clarke and Charlson 1985;Darzi and Winchester 1982;Holmes and Zoller 1996;Hyslop et al 2013;Parrington et al 1983;Parrington and Zoller 1984;Perry et al 1999;VanCuren and Cahill 2002;Zieman et al 1995), LAV (Jaffe et al 2003b;VanCuren 2003;VanCuren and Cahill 2002;VanCuren et al 2005), and WHI (Leaitch et al 2009;McKendry et al 2008). A distinct seasonal cycle with a spring maximum of Ca 2+ concentration can be seen at HPO (~0.25 μg m −3 ; Fig.…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 92%
“…Other studies have reported that in January or February, many elements associated with continental crust experienced an increase in the mass of samples. The aerosol concentration of crustal elements remained elevated until June or July, suggesting that the dust season is from late winter to mid-summer (Parrington et al 1983;Zieman et al 1995). VanCuren et al (2005) concluded that Asian aerosols influence LAV throughout spring, summer, and fall.…”
Section: Dust and Volcanic Emissionsmentioning
confidence: 99%
“…[3] Aerosol transport, including dust from Asia, across the Pacific Ocean, is well documented from low-lying groundbased observations [e.g., Prospero et al, 1985Prospero et al, , 2003Zieman et al, 1995;Arimoto et al, 1996;Huebert et al, 2001;Liu et al, 2006] and elevated mountain sites [Wai et al, 2008]. Asian mineral dust can be transported by the prevailing westerlies in the spring [e.g., Zhang et al, 1997], increasing particulate matter concentrations [e.g., Liu et al, 2006;Park et al, 2008] and pH values of rainwater [Wang et al, 2002] and cloud water in downwind areas.…”
Section: Introductionmentioning
confidence: 99%